Mathematical modeling applied to the analysis of magmatic intrusions thermal influence in Paraná Basin - Rodrigues de Oliveira, Bruno; Corval, Artur; Valente, Sergio de Castro; Lambert, Wanderson; Miranda, Alan Wanderley Albuquerque; de Oliveira, Luiz Gabriel Souza; Fernandes, Victor Hugo (Boletim Paranaense de Geociências, 2022)
This paper has the objective to present equations capable of generating one-dimensional models that permit to quantify the thermal influence caused by igneous intrusions. In Paraná Basin, the petroleum systems were great influenced by igneous activitiesin which they as presented by a thick lava effusion, a large number of dykes in the entire sedimentary section and various levels of sills intruded in stratifications in order to provide thermal energy for organic maturation. Thus, a better understanding of how and how much the intrusions affect the generation of oil and gas is extremely necessary since the knowledge related to the effects of intrusions in such atypical petroleum system is still insufficient. The obtained results show: the thermal influence caused by igneous intrusions is much higher than that proposed in the literature; the presence of multiple intrusions, based on the oil and gas window considered and as a function of it thickness, causes between them, unfavorable thermal influence to the generation of hydrocarbons in small distances and favorable thermal influence in large distances.